EXPERIMENTAL STUDIES ON RADIATION-INDUCIBLE HUMAN TNF GENE THERAPY FOR CANCER - Cao, Xuetao; Zhang, Weiping; Wang, Jianli; Huang, Xin; Qin, Zhihai (Chinese Journal of Cancer Research, 2013)
Tumor necrosis factor (TNF) has certain radioprotective effect on host tissue and is capable of enhancing the antitumor effect of radiotherapy. In addition, the transcriptional regulation of the promoter region of Egr-1 gene is activated by ionizing radiation. So we fused Egr-I promoter with hTNF-ct cDNA, and resultantly constructed a double-copy and radiationinducible retroviral vector named as pETDC. After packaged with Psi-2 and Crip cells in vitro, the hTNF recombinant retroviruses were in the liters of 4×105 CFU/ml. By infection of murine fibroblast cell line NIH3T3 and murine melanoma cell line B16.F10 with the recombinant retrovirnses and followed by G418 resistant selection, two positive clones secreting TNF at the levels of 2.1 ng/ml and 1.1 ng/ml respectively were generated. After exposure to 20 Gy ionizing radiation, TNF secretions from the two positive clones were elevated to 13.8 ng/ml (6.6-fold) and 5.7 ng/ml (5.2-fold) respectively. Furthermore, hTNF-αt exPression in pETDC.transfected cells was confirmed by RT-PCR. These data provide an experimental bases for the application of TNF gene therapy combined with local radiotherapy in cancer patients.